Juncture Patterns of the Surabaya-citizen’s Speech - O.M.F., Karsono (k@ta: A Biannual Publication on the Study of Language and Literature, 2012)
In this paper, the researcher examines juncture patterns of Chinese language of Surabaya citizens who do not use Bahasa or Indonesian language as their mother tongue. The purpose is to see whether juncture patterns of local citizens can resemble the native speakers. The method that is used here is qualitative approach. The research on these juncture patterns is expected to contribute to the pattern map of the Surabaya citizen’s speech in order to develop the Phonology Theory of Juncture. Based on the analysis of ten respondents, producing nine declarative sentences, seven interrogative sentences, six imperative sentences, and four exclamatory sentences, juncture patterns happen sometimes after a subject, after a predicate, between two words, and sometimes between two syllables within a word. Juncture happens before a word when the word is emphasized. The second finding is that juncture between syllables in a word is not always shorter than the one that happens between two words. The last finding is that there are two kinds of juncture, stopping and continuing juncture.